Preclinical evidence and possible mechanisms of cardioprotective effects of resveratrol in diabetic cardiomyopathy: a systematic review and meta-analysis - Xiaodan Yan; Youjia Hu; Shuyuan Zhao; Qian Zhou; Qiu Chen (Diabetology & Metabolic Syndrome)
Abstract Introduction Diabetic cardiomyopathy (DCM) is a significant complication of diabetes, characterized primarily by the development of heart failure in individuals with diabetes. Numerous animal studies have indicated that resveratrol enhances cardiac function in diabetic cardiomyopathy; however, its reliability and underlying mechanism remain unclear. This study aims to assess the cardioprotective effects of resveratrol on DCM and explore its potential mechanism. Methods We searched PubMed, EMBASE, WOS, Cochrane Library, CNKI, CBM, Chinese VIP, and Wan Fang Database until March 31st, 2024, without language restrictions. Continuous outcome measures were analyzed using weighted mean difference or standardized mean difference, and heterogeneity was assessed with I2. The risk of bias in animal experiments was evaluated using the SYRCLE tool, and evidence reliability was determined with the GRADE tool. All data were analyzed using Review Manager 5.4.1 and Stata 17. This study has been registered on the PROSPERO (CRD42024523944). Results A total of 18 studies meeting the criteria were identified. The analysis revealed that the resveratrol intervention group exhibited significant improvements in LVEF (WMD = 17.88), LVFS (WMD = 8.77), HW/BW (SMD=-2.92), SOD (SMD = 4.53), and MDA (SMD=-5.07) compared to the control group. The GRADE grading assessment indicated moderate certainty for LVEF, HW/BW, and MDA, while certainty for other factors was considered low. Conclusion Our research suggests that resveratrol may protect cardiac function in DCM through anti-inflammatory and anti-oxidative stress effects. However, these findings are based on preclinical data, and further extensive trials are needed to confirm their effectiveness and safety before clinical application.